1999
DOI: 10.1111/j.1532-5415.1999.tb01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Catheters: What Type Do Men and Their Nurses Prefer?

Abstract: Both patients and nursing staff prefer condom to indwelling catheters for patient comfort, but they recognize that dislodgment and leaking are major drawbacks of condom catheters. A more secure condom catheter would greatly improve the management of male incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 26 publications
3
48
0
2
Order By: Relevance
“…A randomized trial demonstrated a decrease in bacteruria, symptomatic UTI, and death in patients with condom catheters compared with those with indwelling catheter. 180,[188][189][190][191] Proper techniques for insertion and maintenance of catheters are essential preventative measures. All urinary catheters should be inserted by a trained health care professional using aseptic technique and connected to a closed drainage system.…”
Section: Risk Factorsmentioning
confidence: 99%
“…A randomized trial demonstrated a decrease in bacteruria, symptomatic UTI, and death in patients with condom catheters compared with those with indwelling catheter. 180,[188][189][190][191] Proper techniques for insertion and maintenance of catheters are essential preventative measures. All urinary catheters should be inserted by a trained health care professional using aseptic technique and connected to a closed drainage system.…”
Section: Risk Factorsmentioning
confidence: 99%
“…English-or Spanish-speaking patients arriving for a visit with one of 41 physicians at an urban academic medical center from February 1998 through August 2000 were asked to complete a written alcohol screening test before the physician visit, to assess eligibility for a randomized trial of a systems intervention in primary care (7). Physicians were primary care internal medicine residents and faculty.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteremia occurs in 1% to 4% of those who develop nosocomial bacteriuria (6). Most patients also find an indwelling urinary catheter to be uncomfortable and activity restricting (7). Given these potential morbidities, it is remarkable how infrequently the use of a urinary catheter is documented by a physician's order in the medical record (8).…”
mentioning
confidence: 99%
“…2,3 The urinary catheter is also associated Inserting catheters only for appropriate indications and leavwith other patient safety problems, such as trauma, 4 increased ing in place only for as long as medically necessary is 1 of patient discomfort, 5 and immobility. 6 CAUTI prevention has the strong (category IB) recommendations.…”
mentioning
confidence: 99%